Heterotopia and the city. Public space in a postcivil society. - (:unkn) unknown (Routledge, 2008)
Heterotopie ist ein von Foucault geprägter Begriff, der in der wörtlichen Übersetzung "Andere/Fremde Räume" meint, in der Architekturtheorie und Stadtsoziologie aber derart unterschiedlich verwendet wird, dass es sich der Band zur Aufgabe gemacht hat, den Begriff neu zu klären und die Heterotopien in der heutigen Welt (auf)zusuchen: in Museen, Themenparks, Urlaubsresorts, Gated communities, Wellnesshotels. In den Beiträgen wird das Konzept der Heterotopie noch einmal umfassend theoretisch dargestellt: in einer neuen Übersetzung des Foucaultschen Textes aus dem Jahre 1976, in den Arbeiten seiner Schüler, und in kritischen Fallstudien posturbaner Transformationen von Beaubourg bis Bilbao; sie führen die Debatte zurück auf die Folgen der Privatisierung des öffentlichen Raums.

Heterotopia, literally meaning 'other place', is a rich concept in urban design that describes a space that is on the margins of ordered or civil society, and one that possesses multiple, fragmented or even incompatible meanings. The term has had an impact on architectural and urban theory since it was coined by Foucault in the late 1960s but it has remained a source of confusion and debate since. Heterotopia and the City seeks to clarify this concept and investigates the heterotopias which exist throughout our contemporary world: in museums, theme parks, malls, holiday resorts, gated communities, wellness hotels and festival markets. Theoretical contributions on the concept of heterotopia, including a new translation of Foucault's influential 1967 text, Of Other Space and essays by well-known scholars, the book comprises a series of critical case studies, from Beaubourg to Bilbao, which probe a range of (post)urban transformations and which redirect the debate on the privatization of public space. Wastelands and terrains vagues are studied in detail in a section on urban activism and transgression and the reader gets a glimpse of the extremes of our dualized, postcivil condition through case studies on Jakarta, Dubai, and Kinshasa. Heterotopia and the City provides a collective effort to reposition heterotopia as a crucial concept for contemporary urban theory.
Keywords: Theorie; Raumwissenschaft; Sozialgeographie; Raumforschung; Öffentlicher Raum; Stadtraum; Stadtforschung; Postmoderne; Urbanität